Analysis of the Dualism in Cryptocurrency Regulation in Indonesia - Chandera, H; Safitri, Yosephin Jasmine (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
When discussing the existence of cryptocurrency in Indonesia, the Indonesian government does not recognize cryptocurrency as an official currency of the country. The government classifies cryptocurrency as a tradable commodity. The legal framework for the use of cryptocurrency in economic activities is regulated by two institutions: the Ministry of Trade of the Republic of Indonesia and the Commodity Futures Trading Regulatory Agency (BAPPEBTI), which automatically governs cryptocurrency trading activities. Over time, as cryptocurrency trading activities have increased and even surpassed stock market activities, the government enacted Law No. 4 of 2023 on the Strengthening and Development of the Financial Sector, which grants the Financial Services Authority (OJK) supervisory powers similar to BAPPEBTI. This article will discuss the dualism of supervisory authority over cryptocurrency as a commodity, between BAPPEBTI and OJK. The research is conducted using a normative legal research method with a regulatory approach. The result of this study is that the government should ideally create derivative regulations from Law No. 4 of 2023 on the Strengthening and Development of the Financial Sector to clarify the roles and functions of OJK to avoid overlapping authority with BAPPEBTI. Additionally, a specialized unit should be established to oversee cryptocurrency activities with a structure that involves both BAPPEBTI and OJK in a balanced manner, where both institutions have a proportional share in carrying out their duties.